PENGARUH BUDAYA ORGANISASI DAN PENGEMBANGAN KARIR TERHADAP KEPUASAN KERJA PRAJURIT MELALUI MOTIVASI KERJA DI SATUAN KAPAL AMFIBI KOARMATIM - Cahya Indra Susilo; Indra Prasetyo; Fatimah Riswati (Prodi Magister Manajemen Universitas Wijaya Putra, 2017)
Job satisfaction indicates a conformity between the expectations of a person arising with the rewards provided by the job. In the reality, the unity or object of research has provided or builds the motivation both financially and non-financially, building organizational culture through optimizing the enforcement of Trisila TNI AL to its soldiers optimally. This is done to increase the spirit and commitment and loyalty of soldiers to the duties and responsibilities of the unit. However, job satisfaction of soldiers has not been achieved optimally. The type of this research is explanatory research with quantitative research approach. As the location of research is Unit Amphibious Ship Command Eastern Region. The sample in this study as many as 90 soldiers. The results showed that organizational culture and career development have a significant effect on job satisfaction of Amphibious Warrior Unit of Koarmatim. In addition, organizational culture directly or indirectly can affect job satisfaction, and work motivation can be a mediator of organizational culture in affecting job satisfaction. Besides, career development directly or indirectly can affect job satisfaction, and work motivation can be a mediator of organizational culture in affecting job satisfaction.